Plantar pressures and stabilometry effects of ischemic compression in Flexor digitorum brevis muscle Myofascial Trigger Point: A prepost study - Eva María Martínez-Jiménez; Ricardo Becerro-de-Bengoa-Vallejo; Marta Elena Losa-Iglesias; Eduardo Pérez-Boal; Jorge Posada-Ordax; Anna Sánchez-Serena; Bibiana Trevissón-Redondo; María Benito-de-Pedro; Vicenta Martínez-Córcoles; Israel Casado-Hernández (PLoS ONE, 2025)
Background Ischemic compression is a manual therapy that improves range of motion, pain and disability in Myofascial Pain Syndrome. Plantar foot pain is a common clinical entity that could be due to Flexor digitorum brevis trigger point. Effect on balance and plantar pressures after ischemic compression in Flexor digitorum brevis muscle trigger point have not been checked. Methods Eighteen subjects (aged 25.06 + /- 5.51 years) with bilateral Flexor digitorum brevis latent or active myofascial trigger points were recruited. Study design: pre-post study. We measured three static footprint and stabilometry variables before and after ischemic compression for 90 seconds at bilateral Flexor digitorum brevis Myofascial Trigger Point. A Shapiro-Wilk test was performed to check normality. Comparison of related measures was done by paired T-test or Wilcoxon Range Test depending on whether the distribution was normal or non-normal. Significant differences were considered with p-value <0.05. All statistics were calculated with a 95% confidence interval. Reliability was also assessed with an Intraclass correlation coefficient (ICC) and Standard error measured (SEM) calculation. Results Most variables have good to perfect reliability, with the exception of four variables which had moderate reliability and two variables which had only slight reliability. Reliable stabylometric variables included anteroposterior displacement of COP and surface with EO and EC. The footprint and stabilometry variables showed no significant differences after ischemic compression. Conclusions Ischemic compression in the Flexor digitorum brevis muscle showed no significant differences in plantar pressures and stabilometry. Other techniques like dry needling indicated worsened balance effects. More studies are required to check significant changes. The results are important because they demonstrate a technique to treat FDB MTrP without repercussions on plantar pressure or balance. NCT06509347 (clinicalTrials.gov) initial release 7/7/24 and last release 28/7/24.